Early mannitol administration improves clinical outcomes of pediatric patients with brain edema (Medical Journal of Indonesia, 2018)
Background: Mannitol 20% is used to treat patients with decreased consciousness and as the first line of treatment to reduce intracranial pressure (ICP). However, its application in pediatric patients is still based on minimal evidence. This study was performed to determine the predictive factors of clinical outcomes in pediatric patients with brain edema in the pediatric intensive care unit (PICU). Methods: This prospective cohort study was conducted in the PICU, Sanglah Hospital Denpasar, Bali, Indonesia. The subjects were chosen by consecutive sampling from July 2016 to July 2017. The primary outcome variable was the patient’s clinical outcome. A chi-square test was used to evaluate the association between the timing of mannitol administration and the patient's clinical outcome. Multivariate analysis was performed on all variables with p≤0.25. Results: Forty-one patients were included in the study, 65% of them were male, 65% had good nutritional status, 90% had non-traumatic brain injury, and 73% had confirmed intracranial infection. The risk of sequelae or death for patients in a coma was 1.8 times greater than that of non-comatose patients (p=0.018; CI 95% 1.119–3.047). Based on the timing of mannitol administration from the onset of decreased consciousness, the risk of sequelae or death in patients who received mannitol after 24 hours was 2.1 times higher than that in patients who received mannitol within 24 hours (p=0.006; CI 95% 1.167–3.779). Based on multivariate analysis, only two variables were associated with the patient’s clinical outcome: pediatric Glasgow coma scale (PGCS) ≤3 (p=0.03) and timing of mannitol administration >24 hours (p=0.01). Conclusion: Early administration (<24 hours) of mannitol and high PGCS are related to favorable outcomes in patients with brain edema in the PICU.